Phenomenological study of teenagers wayang fans - Pratama, Andyka Candra (Department of Sociology, Faculty of Social and Political Sciences, Universitas Airlangga, 2023)
Recently, there has been a phenomenon of the existence of wayang fan groups as traditional art among teenagers, which is an element supporting the existence of wayang in the postmodern era. The purpose of this study is to explore the meaning of wayang and the activities of wayang art fans among teenagers. This study used a phenomenological approach by conducting interviews as a data search technique to seven teenager members of Sanggar BALADEWA. The results showed that: (1) the identity of wayang art fans was formed from the background as a ‘puppeteer family' and a ‘fan family' which created differences in meaning in wayang; (2) wayang fans are divided into active fans and passive fans as seen from their activities in Sanggar BALADEWA as a wayang fandom; (3) the existence of wayang for wayang art fans has shifted its function as entertainment due to mass production through digital platforms; (4) Teenagers who are fans of wayang not only have collections related to wayang, but also become ‘dalang muda' as a form of wayang performance production. This study concludes that the art of wayang can adapt to the conditions of the times and there is also a shift in the function of religion to become an entertainment function that contains commercial practices.